An integrative approach to the taxonomy of the crown-of-thorns starfish species group (Asteroidea: Acanthaster): A review of names and comparison to recent molecular data - Haszprunar, Gerhard; Spies, Martin (Zootaxa, 2014)
The scientific names published for species and subspecies in the genus Acanthaster Gervais (Asteroidea: Valvatida: Acanthasteridae) are reviewed, with particular attention to the A. planci species group (crown-of-thorn starfish, COTS). Several problems with earlier nomenclatural and bibliographic data are resolved. The available name for the type species of Acanthaster in the original combination is Asterias echinites Ellis & Solander in Watt, 1786; the often-cited "Asterias echinus" and "Acanthaster echinus" are incorrect subsequent spellings, therefore unavailable. The scientific names and taxonomic concepts for species and subspecies in Acanthaster are compared to recently published, robust COI-barcoding clades. Two of four clades in the A. planci group can be named unequivocally, a third requires a neotype designation to decide which of two available names will be valid, and the fourth clade necessitates a new species description and name. The References section includes annotations explaining bibliographical data important to the nomenclatural evaluations. Many hyperlinks interspersed with the paper’s texts offer quick access to digital versions of the respective references.